2015
DOI: 10.1007/s10096-015-2502-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular seasonal, age and gender distributions of Cryptosporidium in diarrhoeic Egyptians: distinct endemicity

Abstract: Cryptosporidiosis is a worldwide gastrointestinal disease caused by the protozoan Cryptosporidium parasite. It has a broad range of seasonal and age-related prevalence. We aimed to study the molecular prevalence and seasonality of Cryptosporidium over a period of 1 year in a cohort of Egyptian diarrhoeic patients. Stool samples were collected from 865 diarrhoeic patients attending outpatient clinics of Cairo University hospitals, from all age groups over a 12-month period, examined microscopically for faecal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 32 publications
6
25
1
Order By: Relevance
“…The usage of human excreta as manure in crops, open defecation by children in fields and free grazing of cattle along riversides may lead to contamination of river water subsequently used to irrigate fields and for washing the harvest [64] . Most of the Cryptosporidium cases in our study were detected during summer mainly in August (10 cases), and this agreed with other studies from different regions in Egypt [26,27,36,56] . The summer seasonal diarrheal peak may coexist with the increased use of rivers, lakes, swimming pools and water parks [65] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The usage of human excreta as manure in crops, open defecation by children in fields and free grazing of cattle along riversides may lead to contamination of river water subsequently used to irrigate fields and for washing the harvest [64] . Most of the Cryptosporidium cases in our study were detected during summer mainly in August (10 cases), and this agreed with other studies from different regions in Egypt [26,27,36,56] . The summer seasonal diarrheal peak may coexist with the increased use of rivers, lakes, swimming pools and water parks [65] .…”
Section: Discussionsupporting
confidence: 93%
“…We found no significant association between Cryptosporidium infection and history of animal or water contact. Similarly, other reports [7,27] failed to find animal association with Cryptosporidium infection. In a recent report on occupational infection hazards in sewage workers in Alexandria, Egypt, among other protozoa Cryptosporidium rated 15.6% [60] .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, other studies from Rwanda, Malawi, Kenya and South Africa have reported a higher prevalence of cryptosporidiosis at the end of rainy seasons and beginning of the drier months [129, 130]. Studies in Egypt (North Africa) reported a peak prevalence for both Cryptosporidium and Giardia during summer (drier months) with a second peak in winter for Giardia [131, 132]. It is possible that the apparent seasonality of human disease, is reflective of different transmission pathways, hosts, and/or Cryptosporidium and Giardia species in different locations.…”
Section: Molecular Detection and Characterisation Of Cryptosporidium mentioning
confidence: 99%
“…They concluded that CLD affect the immunity of the patients showed significant increase in the incidence of intestinal parasites in cases compared to controls. El-Badry et al (2015) studied the molecular prevalence and seasonality of Cryptosporidium over a period of one year in a cohort of Egyptian diarrhoeic patients. Stool samples were collected from 865 diarrhoeic patients attending outpatient clinics of Cairo University Hospitals, from all age groups over one year, examined microscopically for oocysts by the acid-fast staining method and for copro-DNA detection using nPCR.…”
Section: Proved This Immunologicallymentioning
confidence: 99%